2017
DOI: 10.1016/j.apmr.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cancer Patients in Inpatient Rehabilitation Facilities: A Retrospective Cohort Study

Abstract: Objectives To identify the types of cancer patients admitted to inpatient medical rehabilitation and to describe their rehabilitation outcomes. Design: Retrospective cohort study. Setting U.S. inpatient rehabilitation facilities (IRFs). Participants Adult patients (N=27,952) with a malignant cancer diagnosis admitted to an IRF with a cancer-related impairment between October 2010 and September 2012 were identified from the Uniform Data System for Medical Rehabilitation database. Interventions Not applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 47 publications
6
42
0
1
Order By: Relevance
“…Among brain tumor acute rehabilitation inpatients, return to the primary acute care service rates have been reported between 7.5% and 14.9% . The return to primary acute care service percentage in our LMD group was considerably higher (9/30 or 30%).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Among brain tumor acute rehabilitation inpatients, return to the primary acute care service rates have been reported between 7.5% and 14.9% . The return to primary acute care service percentage in our LMD group was considerably higher (9/30 or 30%).…”
Section: Discussionsupporting
confidence: 73%
“…[16][17][18][19][20] Among brain tumor acute rehabilitation inpatients, return to the primary acute care service rates have been reported between 7.5% and 14.9%. 16,21,22 The return to primary acute care service percentage in our LMD group was considerably higher (9/30 or 30%). However, our LMD study was heavily represented by hematologic malignancies (25/30) and is more consistent with their reported return to the primary acute care service rates of between 26% and 38%.…”
Section: Discussionmentioning
confidence: 72%
“…Acute inpatient rehabilitation (IRF) has been shown in a number of studies to demonstrate statistically significant improvements in functional scores, including general cancer [19‐27], asthenia/deconditioning [8], brain tumor [28‐32], hemipelvectomy for sarcoma [33], oncologic spinal cord injury [34‐36], and paraneoplastic populations [37]. In the IRF setting, the mean length of stay of patients with cancer has been found to be shorter than their cohorts without cancer, including spinal cord injury [38,39] and brain injury [40‐42] comparison studies.…”
Section: Effects Of Acute Cancer Inpatient Rehabilitationmentioning
confidence: 99%
“…Alam et al [61] reported a statistically significant difference of unplanned transfers back to the primary acute care service of 21% of patients with cancer in the IRF versus 9.7% of noncancer‐matched controls. Other studies have reported return to the primary acute care service rates of IRF patients with general cancers between 16.5% and 35% [9,20,21,66‐68]. In most cases, an uninterrupted acute inpatient rehabilitation course with discharge home is considered a successful IRF admission [69,70].…”
Section: Medical Fragilitymentioning
confidence: 99%
“…Mr Zhang has not begun radiation or chemotherapy, so the craniotomy and pathology were likely completed recently. The median survival for GBM is 10‐14 months from the time of diagnosis [4]. Therefore, although death is very possible in the next 6‐18 months, it is likely not imminent.…”
Section: Feature Editor Introductionmentioning
confidence: 99%